CURRICULUM IMPLEMENTATION IN MADRASAH DINIYAH TAKMILIYAH AWALIYAH AT BANDUNG CITY (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
The background of this research is new paradigm in the implementation of the Diniyah Madrasah at this time changes the previous assumption that only as a regular recitation to fill the spare time of children at home after school, becoming a Madrasah Diniyah which aims to supplement Islamic religious education obtained in formal schools in order to increase the faith and devotion of students to God. This study aims to identify the implementation of the Madrasah Diniyah Takmiliyah Awaliyah curriculum at Bandung City. Based on the research, it is expected that the results of the curriculum implementation specifically can be obtained, namely the developed learning design, implementation of learning, assessment of learning, and supervision carried out in the implementation of the Madrasah Diniyah Takmiliyah Awaliyah curriculum at Bandung City. The population in this study was the Madrasah Diniyah Takmiliyah Awaliyah (MDTA) in 30 sub-districts in the city of Bandung with a total of 73 teachers from MDTA. The research method used in this study uses a quantitative approach with the type of descriptive research. The process of collecting data in the field of research uses several techniques in the form of observation, interviews, questionnaires and documentation. The results showed that MDTA teachers had a graduate education background in the Formal Diniyah Madrasah, a non-formal diniyah Madrasah or equivalent education graduates as evidenced by the relevant institution diploma. While from the results of the identification of learning design making, as many as 60% of teachers have difficulty in independently drafting the implementation of Madrasah Diniyah Takmiliyah Awaliyah learning (RPP), Management of the curriculum in the Diniyah Madrasah does not have a curriculum system in teaching and learning activities that are in accordance with the conditions of each each madrasa, the teacher has difficulty in delivering the material because the material has not been systematically arranged, the curriculum provided by the Ministry of Religion is not in accordance with the condition of Madrasahs. This is because the average teacher who teaches at the Diniyah Madrasah does not have a background in teacher education as well as a lack of empowerment and training for teachers.